Prolonged ethanol exposure modulates constitutive internalization and recycling of 5‐HT1A receptors. Issue 4 (29th December 2021) - Wang, Shiyu; Liu, Haoran; Roberts, Jonté B.; Wiley, Aidan P.; Marayati, Bahjat F.; Adams, Kristen L.; Luessen, Deborah J.; Eldeeb, Khalil; Sun, Haiguo; Zhang, Ke; Chen, Rong
Abstract: Alcohol exposure alters the signaling of the serotoninergic system, which is involved in alcohol consumption, reward, and dependence. In particular, dysregulation of serotonin receptor type 1A (5‐HT1AR) is associated with alcohol intake and withdrawal‐induced anxiety‐like behavior in rodents. However, how ethanol regulates 5‐HT1AR activity and cell surface availability remains elusive. Using neuroblastoma 2a cells stably expressing human 5‐HT1ARs tagged with hemagglutinin at the N‐terminus, we found that prolonged ethanol exposure (18 h) reduced the basal surface levels of 5‐HT1ARs in a concentration‐dependent manner. This reduction is attributed to both enhanced receptor internalization and attenuated receptor recycling. Moreover, constitutive 5‐HT1AR internalization in ethanol naïve cells was blocked by concanavalin A (ConA) but not nystatin, suggesting clathrin‐dependent 5‐HT1AR internalization. In contrast, constitutive 5‐HT1AR internalization in ethanol‐treated cells was blocked by nystatin but not by ConA, indicating that constitutive 5‐HT1AR internalization switched from a clathrin‐ to a caveolin‐dependent pathway. Dynasore, an inhibitor of dynamin, blocked 5‐HT1AR internalization in both vehicle‐ and ethanol‐treated cells. Furthermore, ethanol exposure enhanced the activity of dynamin I via dephosphorylation and reduced myosin Va levels, which may contribute to increased internalization and reduced recycling of 5‐HT1ARs, respectively. Our findings suggest that prolonged ethanol exposure not only alters the endocytic trafficking of 5‐HT1ARs but also the mechanism by which constitutive 5‐HT1AR internalization occurs. Abstract : Prolonged ethanol exposure to neuroblastoma cells stably expressing hemagglutinin (HA)‐tagged human serotonin type 1A (5‐HT1A) receptors increases constitutive 5‐HT1A receptor internalization and decreases its recycling, resulting in decreased basal surface 5‐HT1A receptor levels. Moreover, ethanol exposure switches constitutive 5‐HT1A receptor internalization from a clathrin‐dependent to a clathrin‐independent pathway. Changes in the expression and activity of proteins critically involved in endosomal trafficking may contribute to ethanol‐mediated dysregulation of constitutive 5‐HT1A receptor trafficking.